Corpus Linguistics and Corpus-Based Research and Its Implication in Applied Linguistics: A Systematic Review - Ali Mohammed Saleh Al-Hamzi; Ayoub Gougui; Yuni Sari Amalia; Totok Suhardijanto (PAROLE: Journal of Linguistics and Education, 2020)
This article conveys a case-of-systematic survey of outstanding progress on corpora conducted by researchers affiliated with different common-section institutions all over the world.  Such a range overview selected 20 outstanding types of research from multi research-pushing institutions all around the world. These projects employ corpus techniques and technology to treat an enormous domain of research queries that are relevant to linguistic studies, language teaching and learning, cultural studies, and discourse analysis. These varied implementations of corpus techniques and advances clearly explain the great stress and chances that corpora applied in linguistics can hand to those who have the intention to research, educate, and learn the language.